ANALISA PERBAIKAN STRUKTUR RETAK DENGAN MATERIAL GLARE 3 DAN TEKNIK PEREKATAN MEMAKAI METODA NUMERIK DAN VERIFIKASI PENGUJIAN - Hutapea, Boyke
Abstract: The main goal of repairing is to give back structural integrity was decrease before. Optimum repair needs to know structural condition and structural behavior. The objective of the study was to know the use of Glare 3 material with adhesive bonding for repair. Especially to look for stress distribution on the repair material (adherents), and the adhesive as an effect of external load Glare is Fiber Metal Laminate (FML) which is composite material made from high strength aluminum sheet and fiberglass lamina for reinforcing. Glare\'s lower modulus elasticity (E) compare with aluminum will give \'soft patching\' effect. Analysis is worked using Finite Element Method (FEM) with specimen testing for verification. The most aim for testing is to verify stress distribution output from FEM.